(untitled) (Citizenship in Action: Extension and Culture Magazine, 2024)
This article aims to present the relationships established with the development of workshops on mathematics, study and playful approaches, carried out with children from the Aldeia space – Movimento Pró Cultura, a civil society organization, in Limeira-SP, of a sociocultural nature. The workshops were developed by undergraduate students at the School of Technology, FT-UNICAMP, in the context of university extension activities. The activities were programmed with the aim of meeting the demands of children, aged between 7 and 12 years, with difficulties in mathematics, and they underwent several adaptations throughout the workshops, due to the responses to the work carried out. The factors that stood out from this experience and the reflections we make about the work carried out portray a scenario of learning, exchange of knowledge, games and establishment of established relationships between the university and society.